Impementasi Pengendalian Internal Untuk Peningkatan Kinerja Aparatur Sipil Negara Kabupaten Bombana - Jacob Breemer (Fakultas Ekonomi Dan Bisnis, Universitas Pembangunan Nasional Veteran Jakarta, 2025)
This paper aims to determine and analyze the implementation of the government internal control system (SPIP) in improving the performance of the State Civil Apparatus (APBN) at the Bombana Regency Regional Revenue Agency (BPRD). This qualitative research uses a descriptive case study. Five informants, consisting of the Head of the Agency, the Secretary, the Head of the Economic Sub-Division, and the Head of the General Affairs and Personnel Sub-Division of the Bombana Regency Regional Revenue Agency, assisted in the completion of this thesis. Data collection techniques used were observation, interviews, and documentation. The data analysis technique used was an interactive qualitative model. The results of the study indicate that the implementation of the Government Internal Control System at the Bombana Regency Regional Revenue Agency, in accordance with Government Regulation Number 60 of 2008, aims to improve employee performance by prioritizing effective and efficient activities, creating reliable work reports, securing the assets of the Bombana Regency Regional Revenue Agency to support employee performance, and increasing compliance with applicable laws and regulations within the Bombana Regency Regional Revenue Agency. Keywords: Government Internal Control System, ASN Performance. ABSTRAK Tulisan ini bertujuan untuk mengetahui dan menganalisis Implementasi sistem pengendalian internal pemerintah (SPIP) dalam meningkatkan kinerja Aparatur Sipil Negara Badan Pendapatan Daerah Kabupaten Bombana. Penelitian kualitatif ini menggunakan studi kasus deskriptif. Informan penelitian berjumlah lima orang, terdiri dari Kepala badan, sekretaris, kasubag ekonomi, kasubag umum dan kepegawaian Badan Pendapatan Daerah Daerah Kabupaten Bombana telah membantu penyelesaian penulisan tesis ini.. Teknik pengumpulan data yang digunakan adalah observasi, wawancara dan dokumentasi. Teknik analisis data yang digunakan adalah analisis kualitatif model interaktif Hasil penelitian menunjukkan bahwa Implementasi Sistem Pengendalian Internal Pemerintahan pada Badan Pendapatan an Daerah Kabupaten Bombana mengacu pada peraturan pemerintah nomor 60 Tahun 2008 ditujukan untuk meningkatkan kinerja pegawai dengan mengutamakan kegiatan yang efektif dan efisien, membuat lapora kerja yang diandalkan, mengamankan aset Badan Pendapatan Daerah Kabupaten Bombana dalam menunjang kinerja pegawai dan meningkatkan ketaatan terhadap peraturan perundang-undangan yang berlaku di lingkup Badan Pendapatan Daerah Kabupaten Bombana Kata Kunci. Sistem Pengendalian Internal Pemerintahan, Kinerja ASN